Pemberdayaan UMKM Dapoer Fitri di Kecamatan Argomulyo Melalui Pendampingan Pembuatan IUMK dan PIRT untuk Meningkatkan Legalitas Usaha - Wicaksono, Roy Adi; Qurniawati, Rina Sari; Setiawan, Eka; Valentina, Feby; Dwiani, Oktaviana Puput; Fitriani, Fahira; Permataningsih, Farrah Febryanti; Badriyah, Siti; Aisah, Imas Dewi Yanti; Ningrum, Sindi Yuliana Lestari; Annidham, Assakata Sinji (Fakultas Ekonomi dan Bisnis Islam, IAIN Kediri, 2025)
In entrepreneurship, business licensing plays a strategic role in increasing the competitiveness of MSMEs. By having complete legality, MSMEs can gain the trust of consumers, business partners, and financial institutions. Dapoer Fitri is an MSME engaged in snacks. This service activity is designed as a strategic step in empowering MSMEs and assisting in managing business legality, such as Micro and Small Business Permits (IUMK) and Household Industry Food Production Certificates (PIRT). The Service Learning method allows for a reciprocal relationship between students and business actors, where students can apply the knowledge gained in lectures while business actors receive assistance to develop their businesses. The assistance carried out in service has several stages starting from the program planning stage, socialization and information collection, administrative